Molecular characterization of isoprene synthase gene from bacteria - Lamis Muhammad Hossam Eldeen; Haggag Salah Zein; Naglaa A. Abdallah; Nahed Abdelghaffar Abdelaziz (Cairo : Lamis Muhammad Hossam Eldeen, 2017)
Isoprene represents a key building block for the production of valuable materials such as latex, synthetic rubber, pharmaceuticals and serves as basis for advanced biofuels. In this study, the isoprene produced by Bacillus subtilis ATCC 6633 and Bacillus stearothermophilus 12980 ATCC was quantitatively analysed using gas chromatography mass spectrometry (GC-MS). B. stearothermophilus 12980 ATCC produced 1.169 mg/ml isoprene at 55oC for 18h incubation and B. subtilis 6633 ATCC produced 1.071 mg/ml isoprene at 45oC for 18h incubation. Furthermore, heterologous expression of the Kudzu isoprene synthase (kIspS) gene into B. subtilis DSM 402, B. licheniformis DSM 13 using the pHT01 vector and E. coli BL21 (DE3) using the pET28b-C-term to be used as a bench mark. Development of the electroporation protocol for successful tranformations into Bacillus spp. Isoprene production was analyzed using Gas Chromatography Flame Ionization Detector (GC-FID). The highest isoprene production was observed by recombinant B. subtilis harboring the pHT01-kIspS plasmid in which it produced 1275og/l/OD isoprene, that is three-fold higher than the non recombinant Bacillus subtilis (WT) which produced 370 og/l/OD isoprene, when both incubated at 30{u2103} for 48 h induced with 0.1 mM IPTG. Additionally, recombinant B. subtilis produced five fold higher than the recombinant B. licheniformis. Multiple sequnece alignment showed difference in the codon usage analysis between the two Bacillus spp. Recombinant B. subtilis is considered as a versatile host for heterologous production of isopren
Thesis (M.Sc.) - Cairo University - Faculty of Agriculture - Department of Genetics
Issued also as CD
Keywords: Bacillus stearothermophilus; Isoprene; Isoprene synthase